Haemostasis in Spine Surgery - Szpalski, Marek; Gunzburg, Robert; Weiskopf, Richard B.; Aebi, Max (Springer Berlin Heidelberg : Imprint: Springer, 2005)
Blood loss in spine surgery is a significant and very common problem connected with all kinds of surgical procedures. An international faculty of authors provide a comprehensive survey on the research and evidence about blood sparing in spine surgery. This publication fills a gap in the spinal literature and provides invaluable data for all those confronted with blood loss during surgical procedures on the spine.